Development of A Montessori Book to Improve the Early Reading Skills for Elementary School Students - Dessy Dwitalia Sari; Tika Puspita Widya Rini (STAI Hubbulwathan Duri, 2023)
This study aims to (1) produce Montessori reading books and (2) reveal the effectiveness of Montessori reading books in learning to improve the reading skills of first-grade elementary school students. This research is research and development (RnD). The research subjects were students and teachers of grade 1 elementary school. Data was obtained through interviews and observation. The products developed are validated by experts, and initial reading skills are carried out to obtain the effectiveness of the book. Product effectiveness is tested through quasi-experiments. Data analysis techniques used an independent sample t-test with a significant level of 0.05. The results of this study are in the form of Montessori reading books. (1) The results of the expert validation assessment show that the books developed are appropriate according to material experts in the